Aspirin counteracts cancer stem cell features, desmoplasia and gemcitabine resistance in pancreatic cancer - Zhang, Yiyao; Liu, Li; Fan, Pei; Bauer, Nathalie; Gladkich, Jury; Ryschich, Eduard; Bazhin, Alexandr V.; Giese, Nathalia; Strobel, Oliver; Hackert, Thilo; Hinz, Ulf; Gross, Wolfgang; et al. (OncoTarget, 2015)
Pancreatic ductal adenocarcinoma (PDA) is characterized by an extremely poor prognosis. An inflammatory microenvironment triggers the pronounced desmoplasia, the selection of cancer stem-like cells (CSCs) and therapy resistance. The anti-inflammatory drug aspirin is suggested to lower the risk for PDA and to improve the treatment, although available results are conflicting and the effect of aspirin to CSC characteristics and desmoplasia in PDA has not yet been investigated. We characterized the influence of aspirin on CSC features, stromal reactions and gemcitabine resistance. Four established and 3 primary PDA cell lines, non-malignant cells, 3 patient tumor-derived CSC-enriched spheroidal cultures and tissues from patients who did or did not receive aspirin before surgery were analyzed using MTT assays, flow cytometry, colony and spheroid formation assays, Western blot analysis, antibody protein arrays, electrophoretic mobility shift assays (EMSAs), immunohistochemistry and in vivo xenotransplantation. Aspirin significantly induced apoptosis and reduced the viability, self-renewal potential, and expression of proteins involved in inflammation and stem cell signaling. Aspirin also reduced the growth and invasion of tumors in vivo, and it significantly prolonged the survival of mice with orthotopic pancreatic xenografts in combination with gemcitabine. This was associated with a decreased expression of markers for progression, inflammation and desmoplasia. These findings were confirmed in tissue samples obtained from patients who had or had not taken aspirin before surgery. Importantly, aspirin sensitized cells that were resistant to gemcitabine and thereby enhanced the therapeutic efficacy. Aspirin showed no obvious toxic effects on normal cells, chick embryos or mice. These results highlight aspirin as an effective, inexpensive and well-tolerated co-treatment to target inflammation, desmoplasia and CSC features PDA.
Gesehen am 04.01.2019